The response of patients to hospitalization - Đević Rade; Hadzivuković Natalija; Joković Sandra; Pavlović Jelena (Association of Nurses Technicians and Midwives, 2015)
Introduction: It is very difficult to describe how the patient feels at first contact with the hospital environment, medical personnel and medical diagnostic and therapeutic procedures. He was usually upset at first contact since carries with it suspense and feers, due to illnes, but also because of the new situation. Will the first meeting to encourage patients and create confidence and sureness or, derogate and hurt his personality, depends on these first impressions. The aim: The aim is to exemine react to hospitalization, analyze what is to attitude of hospital personnel towards patients, and investigate which patients are proposals to improve the conditions and procedure for hospitalization. Methods: The study was conducted at University Hospital in Foca, period October-November, 2014. The study included 50patients who are being treated at the University Hospital in Foca, in the section of Internal Medicine. The research used an anonymous questionnaire, and the results are graphically presented. Results: Two-thirds of respondents reacted very well to the hospitalization. Asked about their impressions on the first meeting with the medical personnel, 94% of respondents expressed a positive opinion, while 6% of respondents characterized their first meeting as negative. Conclusion: Generally, this study yilded the following results which can be characterized as positive, but we must strive to be better and try to patients satisfaction with the services and attitude of health worker, made at the highest level.